Knowledge, experience, and potential risks of dating violence among Japanese university students: a cross-sectional study - Oishi Kazuyo; Matsuyama Yumi; Shibayama Satomi; Nakao Rieko; Ohnishi Mayumi; Miyahara Harumi (BMC, 2011)
Abstract Background The Domestic Violence Prevention Act came into effect in Japan in 2001, but covers only marriage partner violence and post-divorce partner violence, and does not recognize intimate partner violence (IPV). The present study was performed to determine the experience of harassment, both toward and from an intimate partner, and recognition of harassment as IPV among Japanese university students. Methods A self-administered questionnaire survey regarding the experience of harassment involving an intimate partner was conducted as a cross-sectional study among freshman students in a prefectural capital city in Japan. Results A total of 274 students participated in the present study. About half of the subjects (both male and female students) had experience of at least one episode of harassment toward or had been the recipient of harassment from an intimate partner. However, the study participants did not recognize verbal harassment, controlling activities of an intimate partner, and unprotected sexual intercourse as violence. Experience of attending a lecture/seminar about domestic violence and dating violence did not contribute to appropriate help-seeking behavior. Conclusions An educational program regarding harassment and violence prevention and appropriate help-seeking behavior should be provided in early adolescence to avoid IPV among youth.